Dampak Psikologis Perilaku Phubbing Dalam Berinteraksi Sosial Pada Mahasiswa - Ausani Silmi; Eryanti Novita (Jouska: Jurnal Ilmiah Psikologi, 2022)
The purpose of this study was to find out about the psychological impact of phubbing behavior in social interaction on Medan Area University Students, two of them from the 2018 class and one class 2019. This research is a type of qualitative research using phenomenological methods to deepen one's social interaction when presenting a smartphone in the middle. The interaction takes place face-to-face which leads to phubbing behavior. As well as looking for factors that cause phubbing behavior, the impact of phubbing perpetrators and also victims of phubbing perpetrators. The research respondents were three students. Two of them are phubber or perpetrators and one of them is a victim or called phubbe. The results of this study indicate that the factors that cause phubbing behavior are smartphone addiction, internet addiction, social media addiction, online game addiction, and no control or time limit in smartphone use. The social contact generated by the actor is the dominant negative social contact. Perpetrators tend to be vulnerable when imitating one of the closest people and lose control when after imitating, so that the loss of ethics when interacting directly socially and erodes the nature of sympathy and sensitivity to the surrounding environment. The impact of this behavior is to damage the quality of relationships, decrease mood when interacting socially, not focus, feel neglected, and feel unappreciated.